2015
DOI: 10.1016/j.jhep.2015.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and viral hepatitis

Abstract: WHO estimates reveal that the global prevalence of viral hepatitis may be as high as 500 million, with an annual mortality rate of up to 1.3 million individuals. The majority of this global burden of disease is borne by nations of the developing world with high rates of vertical and iatrogenic transmission of HBV and HCV, as well as poor access to healthcare. In 2013, 3.2% of the global population (231 million individuals) migrated into a new host nation. Migrants predominantly originate from the developing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 67 publications
4
103
0
5
Order By: Relevance
“…It is noteworthy that none of the 1727 immigrants evaluated in the current study and living in Italy for approximately 3 years had been vaccinated. The data of the current study confirmed that HBV screening for immigrants from geographical areas of high or intermediate endemicity was an important preventive measure for public health (37,38).…”
Section: Discussionsupporting
confidence: 74%
“…It is noteworthy that none of the 1727 immigrants evaluated in the current study and living in Italy for approximately 3 years had been vaccinated. The data of the current study confirmed that HBV screening for immigrants from geographical areas of high or intermediate endemicity was an important preventive measure for public health (37,38).…”
Section: Discussionsupporting
confidence: 74%
“…Chu et al, in 2013 [28], found migrants representing a substantial proportion of HBsAg positive and chronic cases in six Northern European Countries. Sharma et al (2015) [11] reported that 53% of HBV carriers were born outside the EU. Finally, among HIV positive migrants, HBV prevalence was reported to be 4.5% in UK [31] and 18.6% in France [7].…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…18,19 Interestingly, many developed countries similarly report suboptimal diagnostic and management rates for chronic HBV infection. [20][21][22][23][24] It is also noteworthy that 19 (1.6%) of our 1214 subjects were found to be coinfected with HCV (i.e., positive for anti-HCV and HCV RNA), another major risk factor for chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%